Belomor: criminality and creativity in Stalin's Gulag - Draskoczy, Julie S. (Myths and taboos in Russian culture, 2014)
Introduction: Born again: a new model of Soviet selfhood -- The factory of life -- The art of crime -- The symphony of labor -- The performance of identity -- The mapping of utopia.